Colorectal cancer diagnosis and screening exams in Brazil during the COVID-19 pandemic: a linear regression model - Tiago de Oliveira Furlam; Luiza Moreira Gomes; Luciana Helena Dolabela de Abreu; Claudia Cristina de Aguiar Pereira; Carla Jorge Machado (Cadernos de Saúde Coletiva, 2025)
Abstract Background: The COVID-19 pandemic negatively impacted the health sector leading to multiple negative outcomes in individual and collective health. Objective: This study aimed to assess the pandemic’s impacts on the performance of diagnostic and screening exams for colorectal cancer (CRC) in Brazil in 2020. Method: Based on Log10 of secondary data from 2008 to 2019, linear regression models were developed. Then, the expected number of colonoscopies, rectosigmoidoscopies, and fecal occult blood tests (FOBT) were calculated for 2020. The projections were compared with the real number of exams in each region and in Brazil in 2020. Results: Most regions presented, from 2008 to 2019, significant decreasing trends in rectosigmoidoscopies, while significant increasing trends in FOBT were found in most regions and in colonoscopies in all regions. None of the regions reached the expected number of any of the procedures in 2020, with the exception to rectosigmoidoscopies in the Midwest. In 2020, compared to the projections, there were found, percentage differences of -39.2% colonoscopies, -40.2% rectosigmoidoscopies and -34.8% FOBT were found for Brazil. Conclusion: The COVID-19 pandemic seems to have negatively affected the performance of exams for screening and diagnosis of CRC in Brazil. Therefore, consequences such as late diagnosis and worse prognosis for patients can be expected in the future.